Fine-scale spatial and temporal variation in earth worm surface casting activity in agroforestry fields, western Honduras - Pauli, N.; Oberthür, Thomas; Barrios, E.; Conacher, A. (Elsevier, 2010)
Quantification of the spatial and temporal distribution patterns of soil fauna is a relatively new area of research, and has been proposed as the key to understanding the high diversity typical of soil fauna communities. Field research on the relationships among the spatial distribution patterns of trees, litter and earthworm surface casting was carried out in two agroforestry fields in a rugged area of western Honduras. Grid-based sampling at a scale of 2–20 m was employed to determine whether any spatial relationships existed among these variables at this fine scale. Each field was sampled twice at either 2 or 3 week intervals, to determine the short-term stability of spatial relationships. The spatial distribution of litter showed a strong pattern of aggregation, whereas earthworm cast distribution did not exhibit strong spatial autocorrelation. However, the spatial distribution patterns of each of these variables were well explained by the spatial arrangement of trees in both sites. Fitted model cross-semivariograms explained between 70% and 90% of the total variation in cross-semivariance between tree density and litter cover, and between tree density and earthworm cast weight. The results of the study suggest that farmers may be able to manipulate populations of earthworms indirectly by managing the spatial arrangement of trees within their crop fields. Planning the distribution of trees could allow farmers to create ‘patches’ of organic resources within fields, while minimising the negative effects of trees on crop growth due to competition for light, water and nutrients. Over the short time scale of the study, unusually heavy rainfall led to substantial changes in spatial distribution patterns of earthworm cast activity and litter cover, which may otherwise not have occurred. This result emphasises the need to take into account short-term temporal change during ecological studies at fine spatial scales.